La educación en tiempos de crisis. Diálogos en torno a lo humano (2021)
This article is the result of reflections on the place of education in times of pandemic from the role of the student. The conversation is situated in educational symmetries and asymmetries in these times of tensions, crises, and social, educational, economic, and political changes. It is then observed that education has changed and will continue to change from the physical space, relationships, teaching methods, curricula, and communications, which invites us to focus on the fragility of the human. Thus, we propose to address four moments: the first one considers the relationship between society and school; the second inquires about the place of the human in education; the third invites us to reflect on education in times of pandemic, as a topic to reconsider; and the fourth addresses a questioning on the type of school we should start talking about. We then reflect on knowledge, practices, and discourses that have been concurring in the current change of era, and on the tensions and dynamics that affect the educational act and, with it, the human experience.